ETIKA PROFESI POLISI DAN KEPERCAYAAN MASYARAKAT: STUDI ATAS INTEGRITAS PENEGAKAN HUKUM - Waljinah, Sri; Wardiono, Kelik; Anggoro, Purwadi Wahyu (Jurnal Ilmiah Advokasi, 2025)
Trust in the performance of law enforcement officers, especially the police, is experiencing a crisis due to several actions taken that are not in favor of the community. This study aims to describe the public's response to the professional ethics of the police in carrying out their duties and authorities. The research data are public opinions regarding the police in carrying out their duties in the community. Data collection was carried out using an in-depth interview method with an accidental technique. Data validation techniques were carried out using triangulation to test the validity of the data. Analysis was carried out using an interactive method based on the results of in-depth interviews. The results of the study are (1) a positive public response to the police in protecting and caring for the community, especially in creating a sense of security from criminal acts in the community, (2) negative public response to the police who still commit irregularities, especially related to the practice of extortion and arrogance in law enforcement, and (3) the implementation of police duties is considered not to be in accordance with the professional code of ethics, so professionalism is required in every implementation of their duties.Keywords: professional ethics; public trust; law enforcement; duties; authority.